International organizations engaging the world / edited by Jan Klabbers, University of Helsinki. - Klabbers, Jan (Cambridge University Press, 2025)
International organizations have always been exclusively seen as vehicles for their member states, exercising delegated powers. This book demonstrates that this picture is seriously outdated: international organizations address a wide variety of social actors, and this needs to be reflected in the way we think about international organizations. The book provides an overview, in distinct chapters, about the sort of actors international organizations engage which; provides empirical examples; investigates potential winners and losers of such interaction, and aims to find ways to come to terms with the realization that international organizations are not solely member state-driven. This title is also available as Open Access on Cambridge Core.